2006
DOI: 10.1074/jbc.m607076200
|View full text |Cite
|
Sign up to set email alerts
|

Translation Elongation Factor 2 Anticodon Mimicry Domain Mutants Affect Fidelity and Diphtheria Toxin Resistance

Abstract: Eukaryotic elongation factor 2 (eEF2) mediates translocation in protein synthesis. The molecular mimicry model proposes that the tip of domain IV mimics the anticodon loop of tRNA. His-699 in this region is post-translationally modified to diphthamide, the target for Corynebacterium diphtheriae and Pseudomonas aeruginosa toxins. ADP-ribosylation by these toxins inhibits eEF2 function causing cell death. Mutagenesis of the tip of domain IV was used to assess both functions. A H694A mutant strain was non-functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
126
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 107 publications
(138 citation statements)
references
References 39 publications
12
126
0
Order By: Relevance
“…Therefore, we wanted to determine whether a general defect in translation would be enough to cause an increase in eIF2␣ phosphorylation levels. Analysis of other eEF1A as well as eEF2 and eEF3 mutants known to affect translation elongation (29,30) showed that increased eIF2␣ phosphorylation does not result from a general reduction in translation elongation (Fig. 1B).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Therefore, we wanted to determine whether a general defect in translation would be enough to cause an increase in eIF2␣ phosphorylation levels. Analysis of other eEF1A as well as eEF2 and eEF3 mutants known to affect translation elongation (29,30) showed that increased eIF2␣ phosphorylation does not result from a general reduction in translation elongation (Fig. 1B).…”
Section: Discussionmentioning
confidence: 97%
“…1B). To determine whether the phosphorylation effect was due to a general inhibition of translation, we analyzed the level of eIF2␣ phosphorylation in eEF2 and eEF3 mutants with established translation elongation defects (29,30). Neither of the eEF2 and eEF3 mutants gave rise to increased eIF2␣ phosphorylation (Fig.…”
Section: Eef1a-ura3p F308l and S405p Strains Exhibit Increasedmentioning
confidence: 99%
“…A recent study on yeast eEF2 mutants provided evidence that diphthamide plays a role in maintaining the fidelity in protein translation on ribosomes (29). The yeast mutant strains lacking diphthamide modification enzymes show modestly increased −1 frameshifting, an effect not due to a reduction in protein synthesis, ribosome binding, or GTP hydrolysis (29). Remarkably, here we found not only OVCA1 −/− MEFs but also eEF2 G717R/G717R MEFs showed significant increases in −1 frameshifting during translation compared with WT cells.…”
Section: Discussionmentioning
confidence: 99%
“…Much analysis has focused on His699, the modified residue (see below) at the tip. Viable mutants that alter His699 or other residues within the tip of domain IV cause modest defects in translational fidelity, including increased programmed 21 frameshifting (Ortiz et al 2006). Analysis of the site of binding of Sordarin, a natural product inhibitor of eEF2, via mutational and structural analyses, has demonstrated that the compound binds between domains I, III, and V of eEF2, matching the sites of Sordarin-resistant mutations (Justice et al 1998;Soe et al 2007).…”
Section: Aa-trna Delivery By Eef1mentioning
confidence: 99%